Detection of pbp2b and ermB genes in clinical isolates of Streptococcus pneumoniae. - Kumari, Navindra; Navaratnam, Parasakthi; Sekaran, Shamala Devi (The Journal of Infection in Developing Countries, 2008)
The characterization of pneumococcal isolates for penicillin and erythromycin resistance genes could be useful to predict the susceptibility of these isolates to other antibiotics, especially beta-lactams drugs. We have developed an assay with a shorter turnaround time to determine the species and resistance profile of Streptococcus pneumoniae with respect to penicillin and macrolides using the Real Time PCR format with fluorescent labeled Taqman probes, hence facilitating earlier and more definitive antimicrobial therapy which may lead to better patient management.